Good booty : love and sex, black & white, body and soul in American music / Ann Powers. - Powers, Ann, 1964- (Dey Street, an imprint of William Morrow, 2017)
"In this sweeping history of popular music in the United States, NPR's acclaimed music critic examines how popular music shapes fundamental American ideas and beliefs, allowing us to communicate difficult emotions and truths about our most fraught social issues, most notably sex and race" -- provided by publisher.